The Effect of Perineal Wound Healing by Giving Duck Eggs, Stripe Fish, Pineapple Juice, Baked Betel Leaves, and Kegel Exercise on Postpartum Women - Sulastri; Ariesti Ramadania; Merta Fellynza; Mustika Reni; Oktafiyanah; Riza Meidiarti (Postgraduate, University of Mataram, 2025)
Perineal wounds are experienced by 75–90% of postpartum mothers in Indonesia and often lead to pain, risk of infection, and delayed recovery. Although pharmacological treatments are available, safer non-pharmacological alternatives are needed. Duck eggs and snakehead fish contain high-quality protein and albumin, pineapple juice provides bromelain with anti-inflammatory properties, boiled betel leaves act as natural antiseptics, and Kegel exercises improve pelvic circulation. This study aimed to analyze the effects of duck eggs, snakehead fish, pineapple juice, boiled betel leaves, and Kegel exercises on perineal wound healing in postpartum women. A quasi-experimental design with intervention and control groups was used. Data were analyzed using univariate and bivariate tests. Independent sample t-tests were applied for normally distributed data, and Mann–Whitney tests were applied for non-normal data using SPSS version 25. Duck eggs, snakehead fish, boiled betel leaves, and Kegel exercises significantly improved perineal wound healing (p < 0.05). Pineapple juice did not have a statistically significant effect (p > 0.05). Natural dietary interventions and Kegel exercises can effectively accelerate perineal wound healing in postpartum mothers. These findings support their use as safe, non-pharmacological options in midwifery care.